Methodology for Research with Early Childhood Education and Care Professionals Example Studies and Theoretical Elaboration - Wallerstedt, Cecilia; Brooks, Eva; Eriksen Ødegaard, Elin; Pramling, Niklas (International Perspectives on Early Childhood Education and Development, 2023)
This open access book addresses the growing trend in the field of early childhood education and care (ECEC) research named collaborative knowledge building in which researchers and ECEC personnel collaborate. This kind of research encompasses a number of approaches, such as design studies, action studies, Learning Studies, Lesson Studies, and combined research and development studies. There are important differences between these approaches, but they also share some features, which makes it possible to see them as examples of a particular tradition of knowledge building. Collaborative knowledge building constitutes close ties between developing practices of early childhood education and care, and generating empirically grounded theoretical knowledge. This book contributes to the methodology of practices-developing research by mapping this movement through exemplifying themes actualised in such studies, and through conceptualizing important and recurring gains and challenges. It also describes how the latter can be taken on.